Human emerging and re-emerging infections : viral and parasitic infections - Singh, Sunit K. (John Wiley & Sons, Inc., 2015)
"Human Emerging and Re-emerging Infections covers the epidemiology, pathogenesis, diagnostics, clinical features, and public health risks posed by new viral and microbial infections. The book includes detailed coverage on the molecular mechanisms of pathogenesis, development of various diagnostic tools, diagnostic assays and their limitations, key research priorities, and new technologies in infection diagnostics."- Resumé vydavatel
Includes index.
Keywords: infekční nemoci; infectious diseases; elektronické knihy; sborníky; electronic books; papers of several authors